Fenomena Arab Spring dalam Wacana Qatar Debate - Mohammad Dzulkifli (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2021)
This article aims to describe the Arab Spring phenomenon through critical discourse analysis of the Qatar Debate. This research is a qualitative descriptive study with the note-taking method. The results of the study show that the structure of the discourse contained in the Qatar debate consists of several structures. First, the macrostructure that contains thematic elements or general themes, namely about ‘Arab Spring has failed’. Second, is the superstructure which contains schematic elements referring to the system and the rules of the game in the turn of speech. Third, the microstructure contains elements of semantics, syntax, stylistics, rhetoric, and metaphors. The semantic element of the Qatar debate shows the uses of language that aims to rever to connotative meanings. Syntactically, the Qatari debaters are dominant using active sentence patterns and noun sentences (jumlah ismiyah). From the stylistic aspect, both teams have their own style of language, as the pro team uses a lot of declarative styles while the counter team tends to use an interrogative style. The rhetorical and metaphorical elements are used a few times but not in large portions. This study also shows the different views of the two teams from two countries that represent the social views of the people in their respective countries towards the Arab Spring phenomenon.Keywords – Arab Spring, Critical Discourse Analyst, Qatar Debate